The Empowerment and Guidance of Religious Life of the Community in Kanagarian Sungai Nyalo Mudiak Aia, Koto XI Tarusan, Pesisir Selatan - Ahmad Rivauzi; Siti Fatimah; Rengga Satria; Ahmad Kosasih; Wirdati Wirdati; Murniyetti Murniyetti (Universitas Negeri Jakarta, 2022)
maritime potential and requires commitment, multi-sectoral support that is developed in a planned, integrated and balanced manner. Tourism development must be able to mobilize all sectors of community life and need to be imbued with the basis of Minangkabau religious, social and cultural norms and must be directed to the preservation of religious and cultural values. The integration of tourism development issues in the Mandeh Region with issues of religious life development is intended so that development can develop in a positive and productive direction. Nyalo Mudiak Aia River. This research uses descriptive qualitative method. Data collection techniques were carried out using interviews, observation and documentation methods. Data analysis in this study used the analytical method by Milles and Huberman in Sugiono (2009:16) which included data reduction, data presentation and conclusion drawing. This study reveals that there are potential candidates for cadres to drive the religious life of the Nyalo Mudiak Aia River community with the community's interest in sending their children to religious schools and colleges. The participation of the government and universities is very strategic in realizing the continuity of good religious life, including in the form of providing facilities (enabling) and empowering in the form of mentoring the religious life of the community.